EDUKASI DAMPAK ANEMIA TERHADAP KESEHATAN REPRODUKSI REMAJA PUTRI DI SMAN 2 PEKANBARU - Lailiyana, Lailiyana; Hindratni, Findy (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2024)
Abstract Adolescent girls are prospective mothers who will give birth to the next generation. One of the health problems of adolescent girls is iron deficiency anemia. As many as 19.4% of teenagers aged 15-24 years in Riau Province experience anemia (Norlita et al, 2023). Anemia in adolescent girls can have a negative impact on the growth and development of adolescents, including the reproductive organs. Anemia in adolescence can continue into adulthood when women become pregnant and give birth. The impact of anemia during pregnancy includes the risk of having an abortion, premature birth, the risk of giving birth to a baby with a low birth weight (BBLR) and stunting. Imbalanced nutritional intake is the main cause of various health problems such as anemia, especially in adolescent girls. Apart from that, a lack of knowledge about foods that contain iron also influences the occurrence of anemia. The aim of this community service activity is to increase the knowledge of adolescent girls about the impact of anemia on reproductive health. The activity was carried out at SMAN 2 Pekanbaru which was attended by 37 grade 11 female students. The method of activity carried out is by providing health education in one meeting for approximately 3 hours including brain storming, games and questions and answers. The material presented is about; anemia, reproductive health, and the impact of anemia on reproductive health. Evaluation of activities is carried out by administering pretest and posttest questionnaires. The results of the activity showed that there was an increase in teenagers' knowledge between before and after being given education, namely from an average score of 8.43 at the pretest to an average score of 9.65 at the posttest. Adolescent girls need to be given regular education about anemia as an effort to prevent anemia in adolescent girls and its impact on reproductive health. Key words: Education, Anemia, Adolescent girls, reproductive health.